Genetics of neuropsychiatric symptoms in patients with Alzheimer's disease: A 1‐year follow‐up study. Issue 12 (8th October 2020) - Huang, Mei‐Feng; Lee, Wei‐Ju; Yeh, Yi‐Chun; Liao, Yi‐Chu; Wang, Shuu‐Jiun; Yang, Yi‐Hsin; Chen, Cheng‐Sheng; Fuh, Jong‐Ling
Abstract : Aim: The aim of this study was to investigate the associations between candidate gene variants and domains of neuropsychiatric symptoms (NPS) and the changes in these associations over a 1‐year period. Methods: Seven hundred and ninety‐three Taiwanese participants (47.8% female) with Alzheimer's disease (AD) were enrolled. Genes associated with a risk of developing AD were selected as candidate genes. NPS were assessed using the Neuropsychiatric Inventory Questionnaire (NPI‐Q), and the NPI‐Q total score and sub‐scores for the Psychosis, Mood, and Frontal Syndrome domains were calculated. Results: Patients with AD and the APOE ε4 allele exhibited more obvious symptoms of psychosis. Mood symptoms were associated with CD33 rs3865444 and EPHA1 rs11767557, and frontal symptoms were associated with SORL1 rs3824968. A 1‐year Time × Alleles interaction effect of CD33 rs3865444 on mood symptoms was discerned. Conclusion: Risk genes of AD, which are also associated with NPS, are APOE ε4 for psychosis, CD33 and EPHA1 for mood symptoms, and SORL1 for frontal symptoms. The association between CD33 and mood symptoms is dynamic and could change over 1 year; however, the results should be interpreted with caution because corrections for multiple comparisons were not performed.